A review of the cicada genus Kosemia Matsumura (Hemiptera: Cicadidae) - Qi, Shengping; Hayashi, Masami; Wei, Cong (Zootaxa, 2015)
The genus Kosemia Matsumura is reviewed based on investigation of the described species and the descriptions of two new species, Kosemia castanea sp. n. and Kosemia guanzhongensis sp. n., from Shaanxi Province, China. Two species formerly belonging to the genus Cicadetta Kolenati, C. chinensis (Distant) and C. mogannia (Distant), are transferred to Kosemia Matsumura to become K. chinensis (Distant), comb. n. and K. mogannia (Distant), comb. n.. The male of K. chinensis (Distant), comb. n. is discovered and described for the first time. Melampsalta bifuscata Liu, 1940 is recognized to be a junior synonym of K. chinensis. Leptopsalta rubicosta Chou & Lei, 1997 and Lycurgus sinensis Jacobi, 1944 are recognized to be junior synonyms of K. mogannia. Kosemia radiator (Uhler, 1896) is removed from the Chinese cicada fauna. A key to species of Kosemia is provided.